Supplementary feeding of calves - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
During 1988 the International Livestock Centre for Africa (ILCA), carried out a number of trials to assess the effect on calves of different types of diet supplementation. Two trials were conducted using Sesbania sesban or Leucaena leucocephala...